Performance and standardization of Australian, Japanese and US firms - Kustin, Richard Alan (Asia Pacific Journal of Marketing and Logistics, 2010)
Purpose – Globalization has fostered greater interest in all aspects of standardization theory including the 4Ps of the marketing mix or program and process marketing. The purpose of this paper is to probe the question: “Is there a benefit to the firm's strategy of marketing standardization that correlates positively to the firm's profit?”. Design/methodology/approach – Multinational firms from Australia, Japan and the USA operating in a global environment were studied in order to correlate marketing standardization to profit performance. Several methods of analysis were used including regression and analysis of variance measures. Findings – The results indicate there is increasing support for a strategy of standardizing marketing mix components and contributing to a firm's profit performance. Originality/value – The paper adds to the current literature by providing further empirical research correlating marketing mix standardization to profit. © 2010, Emerald Group Publishing Limited
5 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/019-893-871-479-303 tex.type: [object Object]
Keywords: Australia; Globalization; Japan; Marketing strategy; Standardization; United States of America; dept.mkt